Nursing Care For Physical Mobility Disorders In Mrs. M With Osteoarthritis At Rojin Home Iryou Houjin Aiwakai Ikeda, En Japan - Farrah Nida Aurelia; Noor Yunida Triana; Ikit Netra Wirakhmi (CV. AFDIFAL MAJU BERKAH, 2026)
Knee osteoarthritis is a major cause of impaired physical mobility in the elderly, especially in facilities such as Japanese nursing homes, with a high prevalence due to aging and obesity. This study aims to describe nursing care for impaired physical mobility in Mrs. M (88 years old) through Range of Motion (ROM) exercises. Using a descriptive single case study design at Ruojin Home Iryou Houjin Aiwakai Ikeda En, Japan (July 2025), the elderly population with knee OA with a single purposive sample (Mrs. M). Instruments included Gordon sheet, NRS pain, MMT, goniometer, observation, and interviews; analysis through narrative nursing process and pre-post chart. The results showed a decrease in pain NRS 2-3 to mild, improvement in antalgic gait, and tolerance to walk 5m x3 without excessive rest after 3 days of passive ROM plus mobilization, although MMT remained 3/5. Conclusion: ROM intervention is effective in improving daily function but requires a longer duration for significant improvement.